Amaranth processing technologies for the production of health-improving food - Stetsenko, Natalia; Simahina, Galina; Goyko, Iryna; Bashta (Sheremet), Alla (My University, 2025)
One of the goals of sustainable development is responsible consumption, in particular, the transition to a significant reduction in waste volumes through the use of measures to prevent its formation, its reduction, recycling and reuse. Such approaches should be implemented in the processing of plant raw materials in modern food technologies, in particular in the production of food products for health and preventive purposes. One of the ways to improve the quality of nutrition of modern people is to introduce food additives with high taste and nutritional qualities into the diet, which include processed amaranth seed products. Researchers are actively developing technologies for the complex processing of amaranth seeds to obtain a number of food and medicinal products from them: products of mechanical and thermal processing, amaranth oil, squalene, CO2-extracts, protein additives and pectin. Products of mechanical processing of amaranth seeds, such as whole-grain flour, are obtained by grinding the seeds on roller mills or disintegrators without removing the seed coat. Extrusion processing helps to reduce the trypsin content and increase the digestibility of the protein, as well as improve the organoleptic properties of the resulting product. Vegetable forms of amaranth and its leafy part are considered as a potential source of coloring pigments, protein and vitamins. The valuable biochemical composition of various parts of the plant creates broad prospects for the use of amaranth in modern food technologies. Однією з цілей сталого розвитку є відповідальне споживання, зокрема, перехід до значного скорочення обсягів відходів шляхом застосування заходів щодо запобігання їх утворенню, їх скорочення, переробка та повторне використання. Такі підходи повинні бути впроваджені при переробленні рослинної сировини у сучасних харчових технологіях, зокрема у виробництві харчових продуктів оздоровчого та профілактичного призначення. Одним зі способів покращення якості харчування сучасної людини є введення в раціон харчових добавок з високими смаковими та поживними якостями, до яких належать продукти переробки насіння амаранту. Дослідники активно розробляють технології комплексної переробки насіння амаранту для отримання з нього низки харчових та лікарських засобів: продуктів механічної та термічної обробки, амарантової олії, сквалену, CO2-екстрактів, білкових добавок та пектину. Продукти механічної переробки насіння амаранту, такі як цільнозернове борошно, отримують шляхом подрібнення насіння на вальцьових млинах або дезінтеграторах без видалення насіннєвої оболонки. Екструзійна обробка сприяє зниженню вмісту трипсину та підвищенню засвоюваності білка, а також покращує органолептичні властивості отриманого продукту. Рослинні форми амаранту та його листова частина розглядаються як потенційне джерело фарбувальних пігментів, білка та вітамінів. Цінний біохімічний склад різних частин рослини створює широкі перспективи для використання амаранту в сучасних харчових технологіях.
Keywords: amaranth; амарант; оздоровчий харчовий продукт; health food product; кафедра технології оздоровчих продуктів